Patriarchy at the helm of gender-based violence during COVID-19 Running title: gender-based violence and COVID-19 - Sumbal Javed; Vijay Kumar Chattu (AIMS Press, 2021)
Gender-based violence (GBV) or violence against women and girls (VAWG), is a global pandemic that affects 1 in 3 women in their lifetime and VAWG is one of the most prevalent human rights violations in the world. The high level of investment going into the COVID-19 recovery plan is a unique opportunity to reshape our patriarchal society, to coordinate across sectors and institutions and to take measures to reduce gender inequalities. Relief efforts to combat the pandemic should take the needs of the vulnerable population, particularly women and girls afflicted by GBV into consideration, as their needs were mostly ignored in the recovery plan of Ebola. GBV is linked to dominance, power and abuse of authority or because any calamity, be it a pandemic, conflict or a disaster. This will further exacerbate pre-existing gendered structural inequalities and power hierarchies as protective mechanisms fail leaves women and girls more vulnerable, fueling impunity for the perpetrators. There is a need for international and domestic violence prevention policies to not only focus on narrowly defined economic or political 'empowerment' because that is insufficient when it comes to challenging existing gender inequalities. Incorporating an individual's religious beliefs and community of faith (mosque, church, temple or synagogue) can offer a support system for an individual and her/his family amid a public health crisis. There is a need to engage men and boys by tailoring messages to challenge gender stereotypes and unequal gender roles to overcome patriarchy.